3D Dewetting for Crystal Patterning Toward Regular Single-Crystalline Belt Arrays and Their Functionality - Wu, Yuchen (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.